PENGARUH PELATIHAN TERHADAP KEMAMPUAN PEGAWAI SATUAN POLISI PAMONG PRAJA KABUPATEN SUMEDANG - Teddy Marliady Nurwan; Annisa Flawerina; Ari Saputra; Nanda Ayu Rifani; Shep Gilang Fauzi; Yeyen Yulianti (JRPA - Journal of Regional Public Administration, 2022)
This study aims to determine employee training, employee abilities, the relationship of training to employee abilities, and the effect of training on the abilities of employees of the Sumedang Regency Civil Service Police Unit.The method used in the preparation of Administrative Research Practice (PPA) is descriptive analysis method. The variables of this study used a variable to be measured from an independent variable training and a dependent variable employee ability. The population in this study was the Civil Service Police Unit of Sumedang Regency, which amounted to 118 employees and a sample of 54 people was taken. The method used is literature study, field study (observation, questionnaire).Based on the results of research on the effect of employee training on the effect of 77.6% (Good) from the ideal criteria with a total score of 4050, and the ability of employees to 84.32% (Very Good), from the ideal criteria with a total score of 4320, the relationship between training and employee abilities is at the highest level. very low correlation with a correlation coefficient of 0.173. Based on these results, it can be said that Hypothesis Ha is accepted, or there is an influence between the training variables on the ability of employees. It is necessary to maintain or develop employee training to be more responsive in assisting employees in their work, this will be beneficial in improving employee abilities.